The scientometric analysis of the research on microalgae-based wastewater treatment - Li, Zhuo; Zhu, Liandong (Environmental science and pollution research international, 2021)
This study explores the characteristics of the literature on microalgae-based wastewater treatment during the past 20 years, based on the Web of Science Core Collection database and its scientometric techniques. The results reveal that the literature on microalgae-based wastewater treatment has grown rapidly with 2621 publications and 54,388 citations in total. Most of the document types are journal articles, constituting 80.7% of the total records. China and the USA are the two most active countries, regarding the publications and cooperation in this filed from the viewpoint of the number of publishing papers, total number of citations, and the number of multinational author papers. The Chinese Academy of Sciences is the largest institutional contributor, publishing 2.3% of the papers, followed by the Indian Institute of Technology (2.2%) and Council of Scientific & Industrial Research (2.1%). The most publishing author is Ruan (35 papers) with the highest number of citation (2460 times). “Bioresource Technology” is the most publishing journal with 365 published papers, while 36.2% of the total sample is published in the subject area of “Environmental Sciences Ecology.” The most cited paper in the past 20 years is a review of the status of phosphorus removal in wastewater by de-Bashan in 2004. Bibliometric analysis has systematically combed the development system of microalgae-based wastewater treatment in the past 20 years and has a great potential to gain valuable insights for the future development, which provides a supplement to the common content analysis.